2013
DOI: 10.9790/2380-0665265
|View full text |Cite
|
Sign up to set email alerts
|

Thermostability of chlorophylls in some native species of xerophytes

Abstract: This study was carried out on eight wild species inhabited the tributaries of wadi Al Noman, at Holey Mecca in the western Kingdom of Saudi Arabia. The plant samples were collected at different locations, where laboratory analyses were included: the water content, chlorophyll content and its stability (CSI), , Mg ions, water soluble sugars and soluble proteins. The results showed that, the chlorophyll a content was higher than the chlorophyll b in the studied species. The maximum value of chlorophylls existed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 19 publications
0
5
0
2
Order By: Relevance
“…In general, the total chlorophyll stability in studied shrubs was higher at xeric habitat compared to those at mesic habitat. Therefore, the increase in CSI and /or chlorophyll contents was referred to the high efficiency of photosynthetic apparatus in plants survives extreme conditions [5]. F values indicated that, the single factors and interactions (with some exceptions) had a significant effects on the CSI a, CSI b and total CSI of investigated species.…”
Section: -Different Metabolites and Mg +2 In Different Specific Speci...mentioning
confidence: 97%
See 2 more Smart Citations
“…In general, the total chlorophyll stability in studied shrubs was higher at xeric habitat compared to those at mesic habitat. Therefore, the increase in CSI and /or chlorophyll contents was referred to the high efficiency of photosynthetic apparatus in plants survives extreme conditions [5]. F values indicated that, the single factors and interactions (with some exceptions) had a significant effects on the CSI a, CSI b and total CSI of investigated species.…”
Section: -Different Metabolites and Mg +2 In Different Specific Speci...mentioning
confidence: 97%
“…had a dominant role on the Mg +2 contents and the habitat factor role was subsidiary. Therefore, the interaction between the environmental factors played the major role on the Mg +2 contents in plants [3]; [5].…”
Section: -Different Metabolites and Mg +2 In Different Specific Speci...mentioning
confidence: 99%
See 1 more Smart Citation
“…Ðå÷îâèíè, ÿê³ âèçíà÷àëè (õëîðîô³ëè, êàðî-òèíî¿äè, ïðîë³í), º ³íäèêàòîðàìè ñòàíó ðîñëèí, à ¿õ âì³ñò ñâ³ä÷èòü ïðî ïåðåá³ã ìåòàáîë³çìó â ðîñëèí³ òà õàðàêòåð âïëèâó çîâí³øí³õ ôàêòîð³â [15][16][17]. Âñòàíîâëåíî (ðèñ.…”
Section: ðåçóëüòàòèunclassified
“…Çàãàëîì ï³äâèùåííÿ âì³ñòó õëîðîô³ë³â ñâ³ä-÷èòü ïðî ï³äâèùåííÿ ³íòåíñèâíîñò³ ìåòàáîë³çìó â ðîñëèí³, àëå äëÿ ïðîöåñó ôîòîñèíòåçó á³ëüø âàaeëèâèì º íå àáñîëþòíèé âì³ñò ï³ãìåíò³â, à ¿õ ñï³ââ³äíîøåííÿ. Âîíè ìîaeóòü ïîêàçóâàòè ïîðóøåííÿ ó ôóíêö³îíóâàíí³ ñâ³òîçáèðàëüíèõ êîìï- ëåêñ³â ³ ðåàêö³éíèõ öåíòð³â ôîòîñècòåì (ñï³â-â³äíîøåííÿ õëîðîô³ë³â à/b), à òàêîae ñò³éê³ñòü õëîðîô³ë³â äî ôîòîðóéíóâàííÿ, ÿêà âèçíà÷àºòüñÿ ê³ëüê³ñòþ êàðîòèíî¿ä³â, çäàòíèõ çàõèùàòè õëîðîô³ëè [16]. Òîìó ðîçðàõîâóâàëè é àíàë³çóâàëè ñï³ââ³äíîøåííÿ âì³ñòó õëîðîô³ë³â à/b ³ õëî-ðîô³ë³â äî êàðîòèíî¿ä³â.…”
Section: ðåçóëüòàòèunclassified